Germination of physic nut seeds in different temperatures, light and substrates Germinação de sementes de pinhão manso em diferentes temperaturas, luz e substratos - Armando da Silva Filho (Semina: Ciências Agrárias, 2012)
The physic nut crop (Jatropha curcas L.) has been gaining some importance in the last years due to its use as a raw material for biodiesel production. The Physic nut can be propagated through stakes and/ or seeds. In this context, it was developed this study in order to evaluate the effects of the substrate, temperature and light on the germination and germination speed index (GSI) of physic nut seeds. The experimental design used was a factorial 4x2x2 with temperature (25, 30, 35 and 40 °C) x substrate (sand and paper) x light (presence and absence) with three replicates per treatment. The best germination percentages were obtained with the temperatures of 25, 30 and 35 °C with light and 30 ºC in light absence for the sand substrate and at a temperature of 30°C, whether in presence or absence of light for the paper substrate. The sowing in sand without light at 30 °C was that best promoted the seedling development with higher GSI. The combination of substrate between sand, temperature of 30 °C and absence of light showed the best condition for evaluating germination and GSI of physic nut seeds. A cultura do pinhão manso (Jatropha curcas L.) vem ganhando destaque nos últimos anos pelo seu uso como matéria prima para a produção de biodiesel. Sua reprodução pode ser realizada por estacas e/ou sementes. Neste contexto, se desenvolveu o presente estudo com o objetivo de avaliar o efeito do substrato, temperatura e luz sob a germinação e índice de velocidade de germinação (IVG) de sementes de pinhão manso. O delineamento experimental utilizado foi o fatorial do tipo 4x2x2 sendo quatro temperaturas (25, 30, 35 e 40 °C) dois substratos (areia e papel) e duas condições de luz (presença e ausência), com três repetições por tratamento. As maiores percentagens de germinação foram obtidas com as temperaturas de 25, 30 e 35 °C com luz e 30 ºC na ausência de luz para o substrato areia. Com a temperatura de 30 °C tanto na presença como na ausência de luz, para o substrato papel. A semeadura entre areia sem luz na temperatura de 30 °C foi a que melhor promoveu o desenvolvimento das plântulas, com maior IVG. A combinação do substrato entre areia, temperatura de 30 °C e ausência de luz é a melhor condição para avaliação da germinação e IVG de sementes de pinhão manso.